PENJADWALAN PROYEK DENGAN PENERAPAN SIMULASI MONTE CARLO PADA METODE PROGRAM EVALUATION REVIEW AND TECHNIQUE (PERT) - Widya Nurul Shofa; Irwan Soejanto; Trismi Ristyowati (OPSI, 2017)
PT At Taqwa Sejahtera has implemented of residential development that duration about 152 day. Due to delay in the supply of primary raw materials, the processing time getting longer or not accordance to planning schedule on October 27, 2017. The project delay have impact on the company which will given punishment.The aim of this study research to the evaluate the project implementation schedule and project scheduling for more optimal time, with the best probability, and minimize the influence of the causes of delays to the project completion time. Project scheduling processing is done by using Program Evaluation Review and Technique (PERT) and implementation with Monte Carlo simulation using Ms Excel software.Based on data processing, the calculation of the project point accelerated time to 147 days with cost Rp 417.315.909,25 and probability of 63%, whereas with the application of Monte Carlo simulus the average conviction rate is at 156 days with cost Rp 402,310,654.25 and probability of 94%.